Meningkatkan Kompetensi Pengetahuan Matematika Melalui Model Pembelajaran Student Facilitator And Explaining Berbantuan Media Papan Pecahan - Keswari, Putu Hita; Ida Bagus Gede Surya Abadi (Universitas Pendidikan Ganesha, 2022)
Students need help understanding math material because students think mathematics is very difficult. It has an impact on student understanding which could be much higher. This research aims to analyze the Student Facilitator and explain Learning Model with the Help of Fractional Board Media on the Competence of Mathematics Knowledge of fifth-grade Elementary School Students. This type of research is quantitative with a quasi-experimental design. The population is 490. The data collection method is the test method using objective tests. The data collection instrument was an objective test in the form of multiple choice. The data analysis technique was descriptive and inferential statistical analysis. The results of the data analysis showed that there were significant differences in the competency knowledge of Mathematics between students who were treated using the student facilitator and explaining learning model assisted by fraction board media and students who were not given treatment in the form of student facilitator and explaining learning model assisted by fraction board media. It was concluded that the student facilitator and explanation learning model with the help of fraction board media positively impacted the competence of Mathematical knowledge. The student facilitator and explaining the learning model with the help of fractional board media can help students learn.